2012
DOI: 10.1590/s1517-83822012000300035
|View full text |Cite
|
Sign up to set email alerts
|

Glucose(xylose) isomerase production by Streptomyces sp. CH7 grown on agricultural residues

Abstract: Streptomyces sp. CH7 was found to efficiently produce glucose(xylose) isomerase when grown on either xylan or agricultural residues. This strain produced a glucose(xylose) isomerase activity of roughly 1.8 U/mg of protein when it was grown in medium containing 1% xylose as a carbon source. Maximal enzymatic activities of about 5 and 3 U/mg were obtained when 1% xylan and 2.5% corn husks were used, respectively.The enzyme was purified from a mycelial extract to 16-fold purity with only two consecutive column ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…The enzyme activity of XIs was inhibited by Ca 2+ . The inhibition with Ca 2+ was also reported by other workers ]. Thin layer chromatography revealed that considerable amount of D‐fructose was formed in 10 min during the isomerization reaction catalyzed by TnapXI.…”
Section: Discussionsupporting
confidence: 82%
“…The enzyme activity of XIs was inhibited by Ca 2+ . The inhibition with Ca 2+ was also reported by other workers ]. Thin layer chromatography revealed that considerable amount of D‐fructose was formed in 10 min during the isomerization reaction catalyzed by TnapXI.…”
Section: Discussionsupporting
confidence: 82%
“…Many microbial strains, including Streptomyces sp. CH7 [17], Lactobacillus bifermentans [18], Bacillus coagulans [19], Streptomyces murinus, Hyperthermophilic Thermotoga [20], and Pseudomonas hydrophila [21], have been reported to produce glucose isomerase. Because of the increased global demand for HFCS, the level of GIase production has gained considerable attention, especially in the food and beverages industry.…”
Section: Owingmentioning
confidence: 99%
“…Similarly, a thermophilic class I enzyme from Thermobifida fusca MBL 10,003 showed Mr = 43.9 kDa (Kasumi et al 2012). Among class I, mesophilic enzyme from Streptomyces sp.CH7 has Mr = 43.6 kDa (Chanitnun and Pinphanichakarn 2012), while hyperthermophilic, class II enzyme from Thermotoga maritima MSB8 has Mr = 45 kDa (Brown et al 1993). It was previously reported that a ~ 1.3 kb (1320 bp) gene (xyl-A) fragment of E. coli K12 encoding for XI of 440 amino acid residues long has a Mr = 44 kDa (Schellenberg et al 1984).…”
Section: Purification Of Ecxi-bl21mentioning
confidence: 99%